Local scattering property scales flow speed estimation in laser speckle contrast imaging. (12th June 2015) - Miao, Peng; Chao, Zhen; Feng, Shihan; Yu, Hang; Ji, Yuanyuan; Li, Nan; Thakor, Nitish V
Abstract: Laser speckle contrast imaging (LSCI) has been widely used in in vivo blood flow imaging. However, the effect of local scattering property (scattering coefficient µ s ) on blood flow speed estimation has not been well investigated. In this study, such an effect was quantified and involved in relation between speckle autocorrelation time τ c and flow speed v based on simulation flow experiments. For in vivo blood flow imaging, an improved estimation strategy was developed to eliminate the estimation bias due to the inhomogeneous distribution of the scattering property. Compared to traditional LSCI, a new estimation method significantly suppressed the imaging noise and improves the imaging contrast of vasculatures. Furthermore, the new method successfully captured the blood flow changes and vascular constriction patterns in rats' cerebral cortex from normothermia to mild and moderate hypothermia.